PENGARUH WEBSITE QUALITY DAN CORPORATE REPUTATION TERHADAP ONLINE REPURCHASE INTENTION - Elissa Dewi Fuastine, - (2023)
This study aims to obtain an overview and influence of website quality and corporate reputation on online repurchase intention on generation Z consumers who use Bukalapak in Indonesia. This research uses descriptive and verifiable methods with a quantitative approach. The sample of this study amounted to 200 respondents who are generation Z consumers who are included in the followers of Bukalapak's official Instagram account in Indonesia. The data is processed statistically with the Structural Equation Modeling (SEM) method. The findings in this study found that the picture of website quality, corporate reputation and online repurchase intention is in the category of quite good. Website quality and corporate reputation have a positive influence on online repurchase intention. This finding shows that the application of website quality and corporate reputation creates an online repurchase intention for generation Z consumers who use Bukalapak in Indonesia.